Divergent dimensions of radicalization risk: migration and violent extremism in Sabah, Malaysia - Boy, Marcus; El-Muhammady, Ahmad; Henkin, Samuel; Nur Ahmad, Hafiza Nur Adheen; Dollah, Ramli; Wan Hassan, Wan Shawaluddin; Singh, Jagroop (University of Maryland, 2020)
This desk study is the product of a collaborative effort undertaken by researchers at the National Consortium for the Study of Terrorism and Responses to Terrorism (START) at the University of Maryland, the International Islamic University of Malaysia (IIUM), and the Universiti of Malaysia Sabah (UMS). It endeavors to provide an account of local dynamics of violent extremism in the Sulu basin and vulnerabilities exploited by regional violent extremist organizations (VEOs) that make the region a hotbed of terrorist recruitment and training. Our initial research suggests that, despite the deficiency of extant research, the threat is especially high in the Malaysian state of Sabah, given its geographic positioning on the northeastern edge of the island of Borneo, sitting just across from western Mindanao and the Sulu archipelago, where a resilient and violent Moro separatist movement (Bangsamoro), as well as a homegrown jihadist movement, have taken root. Recently, these movements have aligned ideologically with the Islamic State (IS), and receive financing, training, and weapons to carry out violent extremism and terrorist objectives in the region. Moreover, VEOs actively exploit existing security vulnerabilities and common drivers of violent extremism in the region.